A Self-Guided Docking Architecture for Autonomous Surface Vehicles - Pedro Nuno Barbosa Leite (2019)
Autonomous Surface Vehicles (ASVs) provide the ideal platform to further explore the many opportunities in the cargo shipping industry, by making it more profitable and safer. Information retrieved from a 3D LIDAR, IMU, GPS, and Camera is combined to extract the geometric features of the floating platform and to estimate the relative position and orientation of the moor to the ASV. Then, a trajectory is planned to a specific target position, guaranteeing that the ASV will not collide with the mooring facility. To ensure that the sensors are within range of operation, a module has been developed to generate a trajectory that will deliver the ASV to a catch zone where it is able to function properly. A High-Level controler is also implemented, resorting to an heuristic to evaluate if the ASV is within this operating range and also its current orientation relative to the docking platform.